ダイ 28 ジ ナンキョク チイキ カンソク タイ ナツタイ ホウコク 1986-1987 - 星合, 孝男; ホシアイ, タカオ; Hoshiai, Takao (1989)
P(論文) 第28次南極地域観測隊は, 隊長星合孝男以下52名で編成された。このうち, 昭和基地の越冬隊は大山佳邦越冬隊長以下29名, あすか観測拠点の越冬隊は鮎川勝越冬副隊長以下の8名である。夏隊は, 隊長星合以下15名で編成され, 運輸省船舶技術研究所, 海上保安庁からの4名, および南極条約に基づく交換科学者として, ベルギーから2名の雪氷学者が同行した。1986年11月14日, 東京港を出港した「しらせ」は, オーストラリアのフリマントル港に寄港した後, 12月17日, ブライド湾に到着し, 物資の輸送, おすか観測拠点における越冬態勢確立のための建設作業を実施した。約300tの物資の揚陸を完了した後, 建設作業を拠点越冬予定者と建設担当の4夏隊員にゆだね, セールロンダーネ山地地学調査隊員(交換科学者2名を含め8名)を残し, 1987年1月5日昭和基地へ向かった。これまでの間に, 第27次越冬隊の指揮下, セールロンダーネ山地の航空写真撮影を行った。昭和基地には1月9日に到着, 輸送(約600t), 建設作業, 野外調査等を1月28日までの間に終了した。2月1日, 越冬交替を行い, 昭和基地在住の第27次越冬隊員27名を収容し, 2月4日, 再びブライド湾に向かい, 5日同地に到着した。一方, 1月末には, あすか観測拠点における越冬の見通しが立ち, 2月12日には予定した夏作業を終了した。第28次夏隊, 交換科学者, 第27次内陸調査隊(8名)を逐次収容した「しらせ」は, 2月15日ブライド湾を離れ, 海洋観測を実施しながら北上, モーリシャスのポートルイス(3月14日-21日), シンガポール(4月3日-9日)を経て, 4月20日東京港に帰着した。 The summer operations of the 28th Japanese Antarctic Research Expedition (JARE-28) in 1986-1987 are described. The icebreaker SHIRASE, carrying 52 expedition members led by the present author, 4 Japanese observers with cargos of about 900t, left Tokyo on 14 November 1986. After calling at Fremantle, Western Australia, where 2 Belgian scientists participated in, the ship arrived at Breid Bay on 17 December. With helicopters unloading of 300t cargos was completed by 5 January 1987. Surface transportation of cargos to and construction of buildings at Asuka Station were concurrently carried out. An aerial photographic survey was also done in the Sor Rondane Mountains region. After departure of the SHIRASE for Syowa Station on 5 January, the construction was continued and the field work of geosciences in the Sor Rondane Mountains region was commenced. The ship reached Syowa Station on 9 January. Relief operations and field research work were completed by the end of January. The SHIRASE left Syowa on 4 February and arrived again at Breid Bay on 6 February. Summer personnel of JARE-28 who completed construction at Asuka and field work in the central part of the Sφr Rondane Mountains region and also the members of inland traverse party of JARE-27 were picked up there by 14 February. ...